2017
DOI: 10.1016/j.vaccine.2016.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulation of synergistic TLR ligands to enhance vaccination against Entamoeba histolytica

Abstract: Diarrheal infectious diseases represent a major cause of global morbidity and mortality. There is an urgent need for vaccines against diarrheal pathogens, especially parasites. Modern subunit vaccines rely on combining a highly purified antigen with an adjuvant to increase their efficacy. In the present study, we evaluated the ability of a nanoliposome adjuvant system to trigger a strong mucosal immune response to the Entamoeba histolytica Gal/GalNAc lectin LecA antigen. CBA/J mice were immunized with alum, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“… 19 21 In previous work, we screened various adjuvant formulations for their ability to generate a Th1-indicating IgG2a/IgG1 ratio in mice after subcutaneous administration with LecA, thus identifying a PEGylated liposomal formulation containing a combination of synthetic TLR4 (GLA) and TLR7/8 (3M-052) ligands as a promising candidate. 22 Further evaluation demonstrated that this adjuvant formulation upregulated production of IFN-γ and IL-17A, 22 cytokines shown to be protective in a mouse model, after subcutaneous administration with adjuvanted LecA. 11 , 23 When administered via alternating intranasal and subcutaneous routes with LecA, the GLA-3M-052 liposome formulation generated functional fecal IgA and 34% protective efficacy as assessed by culturing of parasites from cecal contents in a mouse challenge model of amebic colitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 21 In previous work, we screened various adjuvant formulations for their ability to generate a Th1-indicating IgG2a/IgG1 ratio in mice after subcutaneous administration with LecA, thus identifying a PEGylated liposomal formulation containing a combination of synthetic TLR4 (GLA) and TLR7/8 (3M-052) ligands as a promising candidate. 22 Further evaluation demonstrated that this adjuvant formulation upregulated production of IFN-γ and IL-17A, 22 cytokines shown to be protective in a mouse model, after subcutaneous administration with adjuvanted LecA. 11 , 23 When administered via alternating intranasal and subcutaneous routes with LecA, the GLA-3M-052 liposome formulation generated functional fecal IgA and 34% protective efficacy as assessed by culturing of parasites from cecal contents in a mouse challenge model of amebic colitis.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 23 When administered via alternating intranasal and subcutaneous routes with LecA, the GLA-3M-052 liposome formulation generated functional fecal IgA and 34% protective efficacy as assessed by culturing of parasites from cecal contents in a mouse challenge model of amebic colitis. 22 …”
Section: Introductionmentioning
confidence: 99%
“…In the amebiasis model, the nanoliposome adjuvant containing synergistic TLR4 and TLR7/8 agonists successfully elicited balanced systemic humoral and cellular immune responses. The immunization protected against infection with up to 55% efficacy [115].…”
Section: Role Of Tlrs In Strategies For the Control Of Parasitic Infementioning
confidence: 99%
“…Currently these kinds of vaccines are facing challenges with variabilities in immune response induction [ 57 , 58 ]. Modern vaccination strategies are emphasizing the study of subunit vaccines and proving their effectiveness in immune response modulation [ 59 , 60 ]. Subunit vaccines are characterized by the co-delivery of adjuvants and antigens for immunostimulatory purposes (Fig.…”
Section: Liposome-immune Cell Interactions To Improve Vaccine Effectimentioning
confidence: 99%
“…Finally, a research paper dealing with parasitic infections present us the incorporation of Entamoeba histolytica Gal/GalNAc lectin LecA antigen in liposomal, emulsion and alum formulations containing synthetic TLR agonists adjuvants [ 59 ]. E. histolytica is an anaerobic amoeba and is the etiological agent of amoebiasis, or diarrheal disease commonly transmitted through contaminated water and food sources [ 119 ].…”
Section: Parasitic Infections and Liposomal Vaccinesmentioning
confidence: 99%